Pemetaan Kerawanan Bencana Longsor Menggunakan Teknik UAV (Studi Kasus: Jalur Sitinjau Lauik Padang – Solok) - Akmelliona, Akmelliona; Arif, Dian Adhetya (Al-DYAS, 2024)
One of the most common natural disasters in Indonesia is landslides Heavy rains have caused several landslides in various regions, causing a large impact every year. Landslides caused by rainfall have also become a global problem in many regions, leading to large-scale landslides. Landslides that occur in Sitinjau Lauik, Padang City are influenced by high rainfall with very steep slopes (70˚-80˚), making this area very prone to landslides. One of the techniques used in mapping landslide vulnerability is the Unmanned Aerial Vehicle (UAV) technique, which is a flying machine controlled by a remote controller. The data obtained will be processed using ArcGIS with Weighted Overlay technique, and factors affecting landslides have been conditioned based on Multi Influencing Factor (MIF). This research aims to achieve: 1) the landslide vulnerability level of Sitinjau Lauik Padang-Solok, 2) determine the landslide prone zones in Sitinjau Lauik. The type of research used in this research is quantitative research with spatial approach. The data required are primary data and secondary data. Primary data consists of aerial photographs taken using drones and processed to produce slope, elevation, aspect, and TWI. The secondary data used is the Landsat 8 image in 2023 which is used to determine the vegetation index. This research resulted in 1) The landslide vulnerability level of Sitinjau Lauik is divided into four classes, namely, low landslide vulnerability level with an area of 4342m or 10.81%. Medium landslide vulnerability level with an area of 24575m or 61.16%. High landslide vulnerability level with an area of 11,294m or 28%. And very high landslide vulnerability level with an area of 14m or 0.03%. 2) Landslide vulnerability zonation based on slope condition is divided into 3 zones: Zone A with an area of 20,901m, Zone B with an area of 4642m. And Zone C with an area of 14,614m.